OBSTACLES IN MASTERING ENGLISH: A STUDY OF STUDENTS IN LAHORE DISTRICT - Kalsoom Jahan; Shumaila Ashraf; Sumaira Mukhtar (International Journal of Contemporary Issues in Social Sciences, 2024)
English is an international language and it possesses significant status internationally. It is one of the most common languages and speaks around the world. The syllabus, teaching and learning strategies, lesson planning, and evaluation system all should be designed in such a way that the younger generation would come under ultra-modern educational policy implementation. However, if this implementation initiates at the Secondary level, many young will be able to gain English language competency, and difficulties in English language teaching and learning will be resolved. The researcher designed a questionnaire by surveying different researches. The respondents filled up the questionnaire comprised of four different categories. Several questions were designed under each category that probes the learner’s difficulty in learning English. Likert scale was used research tool. The research was qualitative and qualitative in nature. The data was analyzed through SPPSS by employing a T-test and One Way ANOVA. Afterward, the researcher interpreted findings by comparing and contrasting them with past results. The findings of the first category i.e., curriculum and educational materials, showed current practicing syllabus is outdated and does not fulfill the communicative demands of the ESL learners for their social communication. There is no concept of supplementary material for learning English. The learners rely on textbooks only. The findings of the third category i.e., students’ capacity, revealed that learners are willing to learn the English language but there are certain factors like classroom boredom and lack of opportunities to participate in different activities in class due to large class size.